The ‘God Helmet’ and neuro-spirituality : the pedagogical ramifications for religious and moral education - Shahab, Syed Alwi (2015)
What if we could recreate a religious experience by simply flipping a switch in the brain? What if we could produce the feeling that someone or something is watching over us on demand? According to neuroscientific research conducted with The God Helmet, this may be possible. The God Helmet is the popular name given to a laboratory apparatus called the “Koren Helmet”, after Stanley Koren of Laurentian University’s Neuroscience Department, who built it for Dr. M.A. Persinger, director of the programme. Used as a research tool to investigate the brain's role in religious and mystic experiences, the Koren Helmet has been given the name God Helmet. A few Journalists gave it this name when they learned that some people had visions of God while participating in Koren Helmet experiments. The Koren Helmet is connected to a PC computer through a 'black box' which cycles the signals through four coils on each side of the head over the temporal lobes of the brain. The temporal lobes are the area of the brain many researchers feel is the source of spiritual and religious experiences. The hypothetical question is: Can the God Helmet be used to improve the quality of moral or religious education? This paper discusses this question and suggests a possible line of research to investigate this issue further.